Apakah Kepemimpinan Memiliki Peran Moderasi dalam Kualitas Pengawasan pada Auditor Internal Pemerintah? - Arif, Rizal Nur; Firmansyah, Amrie (Studi Akuntansi dan Keuangan Indonesia, 2023)
This research aims to analyze the influence of competence, independence and integrity on the quality of supervision carried out by auditors at the BPKP Representative Office of Banten Province. This research used 35 Functional Auditor Officials (PFA) at the BPKP Representative Office of Banten Province as respondents. This quantitative research uses SEMPLS with the SmartPLS application as a supporting application in data processing. This research shows that auditor competence has a positive effect on the quality of supervision, while auditor independence and integrity have no effect on the quality of supervision. The research also concludes that leadership does not strengthen the positive influence of the partial relationship between auditor competence, independence and integrity on supervisory quality. It is hoped that the results of this research can provide input for the Banten Province BPKP Representative so that they can implement policies that focus on developing PFA competencies to improve the quality of supervision. This research contributes to the literature on public sector internal auditing, which is still rare in previous research, especially when using Indonesian data. This research also places leadership moderating variables in the relationship between independent and dependent variables, which have rarely been used in previous research.